Essure in Brazil: unveiling senses and social uses of a biomedical device that promised to sterilize women - Brandão, Elaine Reis; Pimentel, Ana Cristina de Lima (Saúde e Sociedade, 2020)
Recently, there have been serious reports of side effects suffered by women in various countries (United States, European countries and Brazil), revealing controversies surrounding Bayer’s widespreaduseofapermanentreproductivecontrol device over the last decade: Essure. This article analyzes the international circulation and the introduction of this biomedical artifact in Brazil. This documentary research investigated websites of regulatory agencies, the aforementioned pharmaceutical laboratory, public disclosure made by hospitals in the country, associated with the Brazilian National Health System. This is the first approach to the subject that questions the social conditions ofthe implementation of Essure in users of these health services when it was available in the country, from 2009 until 2017. This permanent contraceptive method was presented as a safe and easy-to-use clinical management device. The promise of a permanent object that would prevent pregnancy without surgery was sold by Bayer to medical staff as a simple, practical and modern reproductive control solution. Its circulation in Brazil shows medical enthusiasm for the new technique, which was not accompanied by long-term clinical monitoring, even as women began to demand its withdrawal due to the many sequelae and resulting side effects.